Ensuring Natural Grass Sports Fields Are Safe for Athlete Participation: A Risk-Assessment Process for Assessing Field Conditions Before Sports Activity - Lauren A. Petrass; Dara M. Twomey; Caroline F. Finch (Journal of Applied Sports Management, 2016)
Public safety is critical to the provision of sports fields and is dependent on maintaining natural grass surfaces and checking the safety of sports environments before play, to identify, remove and control hazards to reduce injury risk to participants. This paper presents and evaluates a Good Practice Sports Ground Inspection Form (GPSGIF), a new checklist developed to assist sports organizations, policy makers and field managers in the identification of injury hazards on natural grass fields. Use of the GPSGIF led to a consensus decision about the safety of grounds in >80% of assessments, and most items showed high levels of agreement. Comparisons of trained and untrained users showed that untrained assessors had higher levels of agreement, as they tended to rate grounds unsafe, suggesting they erred on the side of caution. The GPSGIF can be used by those responsible for sports field management to make consistent and evidence-informed decisions about field quality. Such assessments will provide athletes with the opportunity to compete in their chosen sport with minimized risk of injury. To enable a more thorough link between field conditions and injury, we would recommend that researchers’ use the GPSGIF in future subjective ground assessment work.
Keywords: safety assessment; safety checklist; injury risk; field conditions; sports injury; ground conditions